2016
DOI: 10.1371/journal.pone.0156421
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Class I Histone Deacetylases (HDAC) by Human Dendritic Cells after Alcohol Consumption and In Vitro Alcohol Treatment and Their Implication in Oxidative Stress: Role of HDAC Inhibitors Trichostatin A and Mocetinostat

Abstract: Epigenetic mechanisms have been shown to play a role in alcohol use disorders (AUDs) and may prove to be valuable therapeutic targets. However, the involvement of histone deacetylases (HDACs) on alcohol-induced oxidative stress of human primary monocyte-derived dendritic cells (MDDCs) has not been elucidated. In the current study, we took a novel approach combining ex vivo, in vitro and in silico analyses to elucidate the mechanisms of alcohol-induced oxidative stress and role of HDACs in the periphery. ex viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Another possible explanation for the enhancement of inflammatory cytokines is interactions between EtOH and NU9056; as we have previously reported in the case of co-treatment of MDDCs with mocetinostat and EtOH, which resulted in the exacerbation of production of oxidative stress related genes 8 . Histone modifications and inflammatory cytokine regulation have been correlated with oxidative and cellular stress as previously reported 53 55 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Another possible explanation for the enhancement of inflammatory cytokines is interactions between EtOH and NU9056; as we have previously reported in the case of co-treatment of MDDCs with mocetinostat and EtOH, which resulted in the exacerbation of production of oxidative stress related genes 8 . Histone modifications and inflammatory cytokine regulation have been correlated with oxidative and cellular stress as previously reported 53 55 .…”
Section: Discussionmentioning
confidence: 88%
“…Buffy Coats are commercially available and each buffy coat represents one N in our experiments. Monocytes were isolated from buffy coats and MDDCs were differentiated as previously described by us 8 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2b, the MDA-MB-231/IR cells exhibited higher GSH levels. Correlating with these results, there was increased expression of antioxidant genes [42] such as NAD(P)H quinone oxidoreductase 1 (NQO1), glutamate-cysteine ligase catalytic subunit (GCLC), glutamate-cysteine ligase modifier subunit (GCLM), thioredoxin reductase 1 (TXNRD1), sulfiredoxin 1 (SRXN1), and microsomal glutathione S-transferase 3 (MQST3) ( Figure 2c). These results demonstrate that, in contrast to MDA-MB-231 cells, MDA-MB-231/IR cells maintained low ROS levels due to their higher expression of ROS scavengers.…”
Section: Mda-mb-231/ir Cells Exhibited Low Ros Levelssupporting
confidence: 58%
“…The involvement of specific HDAC isoforms in alcohol dependence and exposure was investigated in several studies. Recently, results on human primary monocyte-derived dendritic cells, derived from alcohol users, demonstrated that class I HDAC gene expression and protein levels were significantly higher compared to the controls (Agudelo et al, 2016). Another in vitro study revealed that alcohol induced a dose-dependent increase of HDAC2 expression (Agudelo et al, 2011).…”
Section: Epigenetic Mechanisms Of Alcohol Addictionmentioning
confidence: 99%